A Narrative Review on Oral Squamous Cell Carcinoma - Shrikanth Muralidharan; Monali Nikalje; Tulsi Subramaniam; Judy Annie Koshy; Ajit V Koshy; Deepak Bangera (Journal of Pharmacy and Bioallied Sciences)
Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral cavity, accounting for nearly 90% of all oral cancers. It remains a significant global health concern due to the high morbidity and mortality, often diagnosed at advanced stages despite advancements in diagnostic tools such as biopsy, imaging, and molecular markers. OSCC is driven by genetic and molecular alterations, including TP53 mutations, EGFR overexpression, and dysregulated signaling pathways that promote tumor progression. While treatment primarily includes surgery, radiotherapy, and chemotherapy, emerging approaches such as targeted therapy and immunotherapy are showing promise. However, challenges such as recurrence, metastasis, and treatment resistance persist. Improving early detection strategies, identifying novel biomarkers, and incorporating precision medicine approaches are crucial for enhancing survival outcomes and quality of life in OSCC patients.